Preparation of fluorine containing hybrid coatings: investigation of coating performance onto ABS and PMMA substrates - KARTAL, İLYAS; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (WILEY, 2011)
UV-curable fluorinated organic-inorganic hybrid coatings were prepared by the sol-gel technique. Perfluorinated urethane modified alkoxysilane was synthesized by the reaction between perfluoro alcohol and 3-isocyanatopropyltrimethoxysilane. The prepared formulations were applied onto poly(methyl methacrylate) (PMMA) and acrylonitrile butadiene styrene (ABS) panels and polymerized by UV-curing. The properties of the hybrid coatings such as hardness, chemical resistance, thermal stability, surface morphology, double bond conversion, and also contact angle measurements were investigated. Contact angle measurements have shown that the addition of fluorinated silane precursor to the hybrid system improved the water repellency and increased the contact angle from 65 degrees to 106 degrees. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: hybrid coatings; ABS; hydrophobe; UV-curing; contact angle; SOL-GEL COATINGS